Factors Influencing Students’ Academic Performance in Online Courses During the COVID-19 Pandemic - Ruri Nurul Aeni Wulandari; Brillian Rosy; Novi Trisnawati; Jaka Nugraha; Fitriana Rahmawati (Graduate School of Universitas Negeri Malang, 2023)
This study aims to investigate how online learning self-efficacy, self-regulated learning, and achievement motivation affect students' academic performance in online courses during the COVID-19 pandemic. The study participants were students from the Office Administration Education Study Program at Universitas Negeri Surabaya. We used structural equation modeling (SEM) to measure the direct and indirect effects of the structural model. The results show that online learning self-efficacy positively affects self-regulated learning, achievement motivation, and academic performance. However, self-regulated learning and achievement motivation do not affect academic performance, and also do not mediate the relationship between online learning self-efficacy and academic performance.